Exploring blood microbial communities and their influence on human cardiovascular disease - Khan, Ikram; Khan, Imran; Jianye, Zhou; Xiaohua, Zhang; Khan, Murad; Hilal, Mian Gul; Kakakhel, Mian Adnan; Mehmood, Arshad; Lizhe, An; Zhiqiang, Li (Journal of clinical laboratory analysis, 2022)
Background Cardiovascular disease (CVD) is the single biggest contributor to global mortality. CVD encompasses multiple disorders, including atherosclerosis, hypertension, platelet hyperactivity, stroke, hyperlipidemia, and heart failure. In addition to traditional risk factors, the circulating microbiome or the blood microbiome has been analyzed recently in chronic inflammatory diseases, including CVD in humans. Methods For this review, all relevant original research studies were assessed by searching in electronic databases, including PubMed, Google Scholar, and Web of Science, by using relevant keywords. Results This review demonstrated that elevated markers of systemic bacterial exposure are associated with noncommunicable diseases, including CVD. Studies have shown that the bacterial DNA sequence found in healthy blood belongs mainly to the Firmicutes, Bacteroidetes, Proteobacteria, and Actinobacteria phyla. In cardiac events, such as stroke, coronary heart disease, and myocardial infarction, the increased proportion of Proteobacteria and Actinobacteria phyla was found. Lipopolysaccharides are a major component of Proteobacteria, which play a key role in the onset of CVD. Moreover, recently, a study reported the lower cholesterol‐degrading bacteria, including Caulobacterales order and Caulobacteraceae family were both considerably reduced in myocardial infarction. Conclusion Proteobacteria and Actinobacteria were shown to be independent markers of the risk of CVD. This finding is evidence for the new concept of the role played by blood microbiota dysbiosis in CVD. However, the association between blood microbiota and CVD is still inconsistent. Thus, more deep investigations are required in future to fully understand the role of the bacteria community in causing and preventing CVD. In this study, we highlight the origin of the blood microbiota, alteration in the blood microbial makeup, and their association with the etiology and progression of cardiovascular disease.